2015
DOI: 10.4067/s0717-95022015000200032
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Description of the Flexor Digitorum Accessorius Longus Muscle and its Clinical Significance

Abstract: SUMMARY:The flexor digitorum accessorius longus muscle (FDALM) is an anatomical variation that occurs with low frequency in the leg and feet. It was first described by Meckel in 1818. It arises from the tibia or fibula and extends from this towards the quadratus plantae muscle or the flexor digitorum longus muscle, crossing the medial retromalleolar canal and creating a close relationship with the elements of the tibialis posterior neurovascular bundle. A hundred and ten legs were dissected from Caucasian, adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Bilateral FDAL has been identified in cadaveric studies, yet no such case has previously been reported in patients [12][13][14] . Such cadaveric studies report a variation in anatomic characteristics, including number of heads, origins (the inner surface of the flexor retinaculum, tendon sheath of FHL, fibula, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral FDAL has been identified in cadaveric studies, yet no such case has previously been reported in patients [12][13][14] . Such cadaveric studies report a variation in anatomic characteristics, including number of heads, origins (the inner surface of the flexor retinaculum, tendon sheath of FHL, fibula, etc.…”
Section: Discussionmentioning
confidence: 99%